2019
DOI: 10.1177/1941738119868478
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Axillary Nerve Injury in an Elite High School American Football Player: A Case Report

Abstract: An elite high school American football athlete sustained a traumatic, isolated, axillary nerve injury. Axillary nerve injuries are uncommon, but serious injuries in American football. With the advent of nerve transfers and grafts, these injuries, if diagnosed in a timely manner, are treatable. This case report discusses the multidisciplinary approach necessary for the diagnosis and treatment of an elite high school American football player who presented with marked deltoid atrophy. The athlete’s injury was dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…[ 15 16 17 ] These findings have also been further substantiated by cadaveric studies. [ 14 15 16 ] However, there has been a slight discrepancy between the findings established by sonographic studies and those of the cadavers, possibly because these studies have been done in different populations. [ 10 11 12 13 14 15 ] The present study, however, does not use ultrasound findings of the posterior circumflex humeral artery as a guide to course out the axillary nerve because the prime motive of the workers in this study is to establish an affordable cum accessible protocol of a series of safe injection points based on the results of this study for health care workers not only working in tertiary care hospitals with access to ultrasound but also for those workers who deal with vaccinations or therapeutic injections in rural health centers or community health centers where ultrasound is either not accessible or not affordable.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…[ 15 16 17 ] These findings have also been further substantiated by cadaveric studies. [ 14 15 16 ] However, there has been a slight discrepancy between the findings established by sonographic studies and those of the cadavers, possibly because these studies have been done in different populations. [ 10 11 12 13 14 15 ] The present study, however, does not use ultrasound findings of the posterior circumflex humeral artery as a guide to course out the axillary nerve because the prime motive of the workers in this study is to establish an affordable cum accessible protocol of a series of safe injection points based on the results of this study for health care workers not only working in tertiary care hospitals with access to ultrasound but also for those workers who deal with vaccinations or therapeutic injections in rural health centers or community health centers where ultrasound is either not accessible or not affordable.…”
Section: Discussionmentioning
confidence: 69%
“…Some workers have compared the course of the posterior circumflex humeral artery via ultrasound to serve as a route to localize the axillary nerve’s course. [ 14 15 16 ] However, there are still others who have suggested that the posterior circumflex humeral artery need not always accompany the nerve, especially regarding its anterior division as the artery enters the axilla from a posterior aspect. [ 15 16 17 ] These findings have also been further substantiated by cadaveric studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although uncommon, peripheral nerve injuries can be a potentially devastating sports-related injury that may be associated with sensory or motor deficits [91]. Football players are at increased risk, with prior studies demonstrating that between 20% and 30% of all sports-related peripheral nerve injuries occur in American football [62,66,91]. The axillary nerve segment proximal to the quadrilateral space is most frequently associated with shoulder injuries, such as anterior GH joint dislocations and proximal humerus fractures [39,62,85,91,106,114].…”
Section: Diagnosis and Management Of Select Injuriesmentioning
confidence: 99%